2008
DOI: 10.1063/1.3021372
|View full text |Cite
|
Sign up to set email alerts
|

In situ heat treatment of ultrathin MgO layer for giant magnetoresistance ratio with low resistance area product in CoFeB/MgO/CoFeB magnetic tunnel junctions

Abstract: In order to promote the grain growth of ultrathin MgO barrier deposited on a CoFeB layer, in situ infrared (IR) heat treatment just after the deposition of MgO barrier was examined. In case that IR heat treatment was not applied, tunneling magnetoresistance (TMR) ratio of CoFeB/MgO/CoFeB magnetic tunnel junction (MTJ) was significantly decreased with decreasing resistance area (RA) product to less than 10 Ω μm2. On the other hand, TMR ratio of 206% was achieved at the RA product of 2.1 Ω μm2 when the IR heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…6. We use device parameters corresponding to CoFeB MTJ's reported by Diao [6], but assume smaller RA products of the order of 1 Ωµm 2 [8]. Whereas trajectories such as those in Fig.…”
Section: Magnetic Tunnel Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…6. We use device parameters corresponding to CoFeB MTJ's reported by Diao [6], but assume smaller RA products of the order of 1 Ωµm 2 [8]. Whereas trajectories such as those in Fig.…”
Section: Magnetic Tunnel Junctionsmentioning
confidence: 99%
“…These devices not only exceed the required voltage swing threshold, but also reduce the critical switching current density J C to within the order of magnitude needed for CMOS integration. Current efforts are aimed at reducing the resistance-area (RA) product of high TMR MTJ's in order to decrease power dissipation and noise [8]. In addition, to further reduce J C at reasonably fast pulsewidths without sacrificing thermal stability [9,10], material development and careful device design are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have indicated that a single atomic layer of crystalline Fe at the interfaces of a crystalline MgO barrier should be sufficient to achieve a giant TMR ratio [15]. Heat treatment also enlarges the grain size and reduces defects in the MgO barrier [16], supposedly contributing to the observed increase of the TMR ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The development of magnetic tunneling junctions (MTJs) mainly concentrates on raising magnetoresistance ratios (MR) while reducing the values of the resistance-area product (RA) [1,2]. To measure MR and RA values, the blanket wafers must usually be patterned into devices.…”
Section: Introductionmentioning
confidence: 99%